2018
DOI: 10.1016/j.paid.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Events associated with stability and change in adult locus of control orientation over a six-year period

Abstract: Although locus of control (LOC) has been the focus of thousands of studies we know little about how or if it changes over time and what is associated with change. Our lack of knowledge stems in part from the past use of cross-sectional and not longitudinal methodologies to study small numbers of participants from non-representative populations. The purpose of the present study was to use a longitudinal design with a large representative population to provide relevant information concerning the stability and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…With regard to life-events, LOC did not predict the number of PLEs or NLEs (in line with work by Cobb-Clark and Schurer, 2013), although concurrently, life-events were predictive of LOC. In line with previous work our results indicate that NLEs precede changes towards a more external LOC (Nowicki et al, 2018). Life-events also predicted changes in severity of anxiety and depression symptoms, in line with previous reports (Kinderman et al, 2013;Spinhoven et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regard to life-events, LOC did not predict the number of PLEs or NLEs (in line with work by Cobb-Clark and Schurer, 2013), although concurrently, life-events were predictive of LOC. In line with previous work our results indicate that NLEs precede changes towards a more external LOC (Nowicki et al, 2018). Life-events also predicted changes in severity of anxiety and depression symptoms, in line with previous reports (Kinderman et al, 2013;Spinhoven et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Gradual changes towards a more external LOC over a period of eight years were also observed in a sample of women aged 32-46 years (Doherty, 1983), and in ageing samples more generally (Lachman, 2006;Lang and Heckhausen, 2001). In contrast, Nowicki et al (2018) found that women developed a more internal LOC in the period from pregnancy to motherhood, whereas their partners developed a slightly more external LOC. In addition, a significant change towards a more internal LOC was found in middle-aged psychiatric inpatients with a depressive or anxiety disorder diagnosis after treatment with cognitive behavior therapy, and this improvement was maintained over a three-month follow-up (Page and Hooke, 2003).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These findings suggest that LoC may be an amenable target for interventions aimed at increasing internality, to improve cognitive function in adulthood and consequently, help to reduce risk of ageing-related morbidity (including Alzheimer’s disease, which has been consistently associated with lower cognitive function in mid-life and mortality [23,24]). Several studies have provided evidence that LoC is modifiable, with cognitive training interventions increasing internality [1517], and Nowicki et al [25] have identified several factors associated with changes towards both internality and externality. Our study identified a subgroup of participants (~30%) whose LoC changed over time (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been ten publications using ALSPAC data on parental LOC, summarized in Table 6 , and include both analyses identifying antecedent factors [25] , [26] , [27] , [28] and consequences [18] , [29] , [30] , [31] , [32] , [33] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%